2012
DOI: 10.1152/ajplung.00293.2011
|View full text |Cite
|
Sign up to set email alerts
|

Improved pulmonary vascular reactivity and decreased hypertrophic remodeling during nonhypercapnic acidosis in experimental pulmonary hypertension

Abstract: Christou H, Reslan OM, Mam V, Tanbe AF, Vitali SH, Touma M, Arons E, Mitsialis SA, Kourembanas S, Khalil RA. Improved pulmonary vascular reactivity and decreased hypertrophic remodeling during nonhypercapnic acidosis in experimental pulmonary hypertension. Am J Physiol Lung Cell Mol Physiol 302: L875-L890, 2012. First published January 27, 2012; doi:10.1152/ajplung.00293.2011.-Pulmonary hypertension (PH) is characterized by pulmonary arteriolar remodeling with excessive pulmonary vascular smooth muscle cell (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 79 publications
(179 reference statements)
1
19
0
1
Order By: Relevance
“…A possible implication of these observations is that benefits of CO 2 were related to acidosis, rather than to hypercapnia, in keeping with recent findings in adult animals by Christou et al (9). Furthermore, in short-term lung injury models, normalizing pH by buffering has been shown to worsen injury (36) where inhaled CO 2 has otherwise been protective (38, 64, 72).…”
Section: Discussionsupporting
confidence: 74%
“…A possible implication of these observations is that benefits of CO 2 were related to acidosis, rather than to hypercapnia, in keeping with recent findings in adult animals by Christou et al (9). Furthermore, in short-term lung injury models, normalizing pH by buffering has been shown to worsen injury (36) where inhaled CO 2 has otherwise been protective (38, 64, 72).…”
Section: Discussionsupporting
confidence: 74%
“…These cellular processes account for increased medial and adventitial thickening of the arterial wall leading to pathological obstructive changes in the pulmonary microvasculature of the diseased. 2,3 Recently, activin receptor-like kinase 1 (ALK-1), an EC receptor for the transforming growth factor-β (TGF-β) family has been implicated in the pathogenesis of PH. ALK-1 mRNA has been reported to be most abundantly expressed in rat lungs as well as in kidney, brain, and heart.…”
Section: Introductionmentioning
confidence: 99%
“…), rat pulmonary arteries (Christou et al . ) and rabbit mesenteric arteries (Nakanishi et al . ) and aorta (Celotto et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well known that pH i plays crucial roles in determining vascular tone (Wakabayashi et al 2006), the reported effects of acidosis on vascular tone are inconsistent and even conflicting. It has been reported that acidosis produced vasodilatation or inhibition of contraction in many vascular beds, including human internal mammary arteries (Rohra et al 2005), porcine cerebral (Kokubun et al 2009), coronary (Ishizaka & Kuo, 1996) and pulmonary arteries (Nilsson et al 2012), rat pulmonary arteries (Christou et al 2012) and rabbit mesenteric arteries (Nakanishi et al 1996) and aorta (Celotto et al 2011). On the contrary, it has also been reported that acidosis induced contraction in rabbit pulmonary (Ketabchi et al 2009), basilar (Cho et al 2007) and mesenteric arteries (Nakanishi et al 1996), rat coronary artery (RCA; Phillis et al 2000) and aorta (Furukawa et al 1996) and dog coronary artery (Goodyer et al 1961).…”
Section: Introductionmentioning
confidence: 99%